Status of comprehensive treatment for locally advanced colon cancer - Wu Xiaocai; Yin Lu (结直肠肛门外科)
Locally advanced colon cancer includes stage Ⅲ and high-risk stage Ⅱ colon cancer (with tumor invasion depth of T4 stage). Both national and international guidelines recommend surgery as the primary treatment, followed by adjuvant chemotherapy. However, even with standardized treatment executed, up to 30% of patients still experience recurrence and metastasis. Therefore, strategies to improve the prognosis of patients with advanced colon cancer remains a focal point of research. Most completed and ongoing clinical trials haved focused on neoadjuvant therapy. Unlike rectal cancer, there is not an laternative to sugery when treating locally advanced colon cancer, even after comprehensive neoadjuvant therapy. This article provides a literature review on the current status of comprehensive treatment of locally advanced colon cancer.